The Following Variables Are Linked to the Prevalence of Chronic Energy Deficiency in Expectant Mothers - Sumarni (Bulletin of Inspiring Developments and Achievements in Midwifery, 2025)
Women who are expecting and who have chronic energy deficiency (CED) are at risk for significant nutritional problem because it contributes to high maternal morbidity and mortality rates as well as fetal growth disorders. This study aims to analyze the relationship between knowledge level, economic status, and the prevalence of CED in expectant mothers at Puskesmas Balai Selasa Pesisir Selatan Regency in equal measure. The study used a cross-sectional analytical design. A sample of 66 pregnant women in the second and third trimesters was obtained using accidental sampling techniques. Data were collected through questionnaires and measurements of the Upper Arm Circumference (MUAC), then examined using the chi-square test both univariately and bivariately. The findings indicated that 42.4% of pregnant women experienced CED. There was a significant relationship between knowledge level (p = 0.000), economic status (p = 0.000), and parity (p = 0.001) with the incidence of CED. It can be concluded that these three variables are risk factors for CED. It is anticipated that healthcare professionals will strengthen nutritional education and interventions that focus on high-risk groups